Pengaruh Performa Termal pada Double Serpentine Minichannel Liquid Cold Plate dengan Fluida Kerja Air - Litania Kusumaningrum; Indro Pranoto (Prosiding Seminar Nasional Teknoka, 2023)
Temperature is the main cause of failure of electronics and electric vehicles (EV). This condition causes thermal runway, which is a condition where the amount of heat generated by the battery continues to increase so that it is not controlled. To overcome this condition, an effective cooling system is needed, one of which is a liquid minichannel cold plate. The purpose of this research is to determine the performance of double serpentine with water fluid in a liquid cold plate cooling system. This research uses a double serpentine liquid minichannel cold plate with dimensions 104 × 80 × 11 mm with aluminum . Using a channel width of 0.5 mm with a depth of 4 mm, so as to obtain a hydraulic diameter of 0.889 mm. The flow rate variations used are 1 LPM; 1.25; and 1.5 LPM. In addition, this study varies the power from 10 W to 90 W with an increase of 20 W. The results of this study show that the flow rate affects the heat transfer coefficient. The greater the flow rate value, the higher the heat transfer coefficient value produced. The increase in the value of this coefficient affects the decrease in surface temperature. The increase is shown in the condition of 1 LPM value ( ) worth 0,39 kW/m2 K; 1.25 LPM value ( ) worth 0,44 kW/m2 K; while for 1.5 LPM value ( ) worth 0,52 kW/m2 K. In addition, the flow rate also affects the increase in pressure drop. The increase is shown in the condition of 1 LPM pressure drop value of 137,89 kPa; 1.25 LPM of 165,47 kPa, and 1.5 LPM of 199,94 kPa.